FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN TOTAL ANGKA BAKTERI DAN KEBERADAAN BAKTERI Escherichia coli PADA ALAT MAKAN (STUDI PADA LAPAS KLAS I KEDUNGPANE KOTA SEMARANG) - Shofi Nazilatul Rizqi; Retno Hestiningsih; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Morbidity due to foodborne disease caused by poor hygiene and sanitation. One reason is the condition of utensils that unhygienic. The results of the study in 2012 said there was a difference of bacterial contamination on sanitary good tool that was equal to 33.3%. The research was done in prisons Class I Kedungpane Semarang which aims to analyze the microbiological contamination of feeding equipment in prisons Class I Kedungpane Semarang. This type of research is explanatory research with cross sectional approach. The sample in this study were taken on each block in prisons using purposive sampling techniques and be obtained a number of 82 samples. Data were collected through interviews and laboratory tests then analyzed using univariate and bivariate analysis. Bivariate analysis using chi square test. The results of microbiological examination showed that there were 70.7% positive samples eating utensils contaminated E. coli and 62.2% of samples tableware eligible total number of bacteria. Statistic test results indicate variables related to the presence of E. coli were tableware washing technique (p = 0.005) and tableware storage techniques (p=0,041), while the variable related to the total number of bacteria were health condition (p=0.001), hand hygiene (p=0.019), tablewarewashing technique (p=0.004) and tablewarestorage techniques (p=0,014). Suggestions from this research that the prison is expected to improve hygiene and sanitation facilities by providing support facilities cleanliness considering most facilities in poor sanitary conditions.